(untitled) (International Journal of Multidisciplinary Research and Explorer, 2021)
Compost is a simple way of creating what scientists call a positive feedback loop. This study was conducted to determine the pH, N, P, and moisture content; the number of days to decomposition; the percent recovery of composted substrates; and the return on cash expense of producing the formulated sunflower-based compost. The substrates used in the study were wild sunflower, grass, alnus leaves and banana bract. These were composted until it becomes recognizable. The grass, alnus leaves, and banana bract are constant in weight which is 10 kg each, only the sunflower varied in rate. Different rates of wild sunflower in the treatments were the following: T1=10 kg, T2=20 kg, T3=30 kg, T4=40 kg and T5=50 kg. Results showed that chemical and moisture contents of formulated wild sunflower-based compost were not affected by the different rates of wild sunflower except N. Treatment 4 (4:1:1:1 of wild sunflower, grass, alnus leaves and banana bract) obtained the highest N content with 3.21 %. The lowest was registered from the formulation of 1:1:1:1 of wild sunflower, grass, alnus leaves and banana bract (T1) with 2.21 %. The higher the rate of wild sunflower, the early and the higher are the number of days to decompose and the percentage of its recovery, respectively. Treatment 5 (5:1:1:1 of wild sunflower, grass, alnus leaves and banana bract) gained a higher return on cash expense with 13.05 %.